Supraclavicular artery island flap for head and neck reconstruction - Şahin, Bayram; Ulusan, Murat; Başaran, Bora; Güneş, Selcuk; Oymak, Emre; Genç, Selahattin (Acta chirurgiae plasticae, 2021)
BACKGROUND: The ablative surgical resection has a critical importance for achieving better oncological outcomes for patients with head and neck cancer. However, radical surgical resections reveal the reconstruction requirement of complex anatomical structures. Microvascular free flaps have been recommended as a gold standard treatment choice for head and neck reconstruction following definitive oncological surgery. The supraclavicular artery island flap (SCAIF) is a thin and reliable fasciocutaneous pedicled flap that is simple and quick to harvest. MATERIAL AND METHODS: A total of 19 patients who underwent head and neck reconstruction with SCAIF were included in this study. The SCAIF was used for the reconstruction of oncological defects in 17 patients while it was used for the reconstruction of a skin defect on the lower face following radiotherapy in 1 patient and for cervical open wound (blast injury) closure in 1 patient. RESULTS: There were neither intraoperative nor postoperative major complications in any patient. The SCAIF has been used successfully in 18 of 19 patients for head and neck reconstructive surgery. Partial necrosis of the skin was detected in 1 patient (5.3%) only, while a total flap failure has not occurred in any patient. The partial skin necrosis was seen in an area of 1.5 cm of the distal end of the flap and was managed conservatively with local wound care. Wound dehiscence has not appeared in the flap donor area in any patient. CONCLUSION: The SCAIF constitutes a good alternative to free flaps, providing almost equivalent functional results and requiring less operative time and surgical effort.
Keywords: supraclavicular artery island flap; Humans; head and neck reconstruction; krk; pedicled flap; lidé; Plastic Surgery Procedures; fasciocutaneous flap; nádory hlavy a krku; Head and Neck Neoplasms; head and neck cancer; arterie; Arteries; zákroky plastické chirurgie; Retrospective Studies; Neck; retrospektivní studie; volné tkáňové laloky; Free Tissue Flaps